Phospholipase Cε Hydrolyzes Perinuclear Phosphatidylinositol 4-Phosphate to Regulate Cardiac Hypertrophy - Zhang, Lianghui (2013)
Phospholipase Cε (PLCε) is a multifunctional enzyme implicated in cardiovascular, pancreatic and inflammatory functions. Here we show that conditional deletion of PLCε in mouse cardiac myocytes protects from stress-induced pathological hypertrophy. PLCε siRNA in ventricular myocytes decreases endothelin-1 (ET-1)-dependent elevation of nuclear calcium and activation of nuclear protein kinase D (PKD). PLCε scaffolded to muscle-specific A kinase anchoring protein (mAKAP), along with PKCε and PKD, localizes these components at or near the nuclear envelope and this complex is required for nuclear PKD activation. Phosphatidylinositol 4-phosphate (PI4P) is identified as a perinuclear substrate in the Golgi apparatus for mAKAP-scaffolded PLCε. We conclude that perinuclear PLCε, scaffolded to mAKAP in cardiac myocytes, responds to hypertrophic stimuli to generate DAG from PI4P in the Golgi apparatus, in close proximity to the nuclear envelope, to regulate activation of nuclear PKD, and hypertrophic signaling pathways.